Edukasi Perilaku Hidup Bersih Dan Sehat (PHBS) Masa Adaptasi Pasca Pandemi Covid-19 Bagi Siswa-Siswi Sdn 010 Kecamatan Samarinda Utara - Rita Puspa Sari; Ruminem; Dwi Nopriyanto; Ida Ayu Kade SW (Jurnal Pengabdian Kesehatan Masyarakat Mulawarman, 2023)
ABSTRACT Activity Objectives The purpose of this educational activity is to increase the knowledge of SDN 010 North Samarinda sub-district students about clean and healthy living behavior (PHBS) and to teach clean and healthy living habits both in the school environment and in the family environment. The method used to achieve the objectives of community service activities is counseling or health proportions in the form of an explanation of clean and healthy living behavior (PHBS). The results obtained after the community service activities were carried out, namely increasing students' knowledge about the principles of clean and healthy living behavior (PHBS), are expected to be able to change the attitude of students towards the importance of applying the principles of clean and healthy living behavior, students are able implementing clean and healthy living behaviors in the school environment as well as in the home/family environment, UKS supervisor teachers know more about how to teach PHBS principles to students and how to create a healthy environment at school, including canteens that meet health requirements and at later stage students are expected to be able to set an example PHBS behavior and as an agent of change to spread knowledge about PHBS in the family environment and the wider community. Keywords: Education, PHBS, Students